PENGARUH PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAPA KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V PEKANBARU - Rani Aulia Putri; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
AbstractThis research aims to know the influence of career development and work environment on performance of employees PT. Perkebunan Nusantara V Pekanbaru. In PT. Perkebunan Nusantara V Pekanbaru, the magnitude of the responsibilities that must be assumed but is not accompanied by the authority in making its decision, this would mean excessive supervisor intervention up to the technical aspects, the standard operating procedures that are too rigid thus making the employees not motivated to find or make decisions faster and employees also saturated to follow a standard that has been established so that the impact on the decline in the performance of the employee. In determining the subject will be examined, researchers use accidental sampling. accidental sampling means the sample determination technique based on respondents who found by investigators at the time of data collection, the sample in this research will be taken on the employees of PT. Perkebunan Nusantara V Pekanbaru year 2017 with the number of employees as many as 82 people. The method in this research is the analysis of multiple linear, t-test and f-test with the help of SPSS ver 24 applications for windows. This research concluded that the test results showed that the career development t against the performance of an employee the existence of significant influence on performance of employees at PT. Perkebunan Nusantara V Pekanbaru. T test results indicate that the work environment on performance of employees of the existence of significant influence on performance of employees at PT. Perkebunan Nusantara V Pekanbaru. F test results indicated that career development and work environment simultaneously significantly influential on performance of employees received.Keywords: Career Development, Work Environment, Performance